A Patient with Splenic Artery Aneurysm Rupture and the Importance of Rapid Sonography in the ED - Masayuki Iyanaga; Susan Watts; Takeshi Kasai (Emergency Medicine International)
We report a case of a splenic artery aneurysm rupture presenting with shock which required timely embolization therapy. This case demonstrates how the rapid use of bedside ultrasound by emergency department (ED) physicians can help identify the cause of shock and, therefore, initiate appropriate treatment quickly even if the cause is rare, as in this case.